ADDED ADVANTAGE OF INJECTING SUBTARSAL STEROID INJECTION AFTER INCISION AND CURETTAGE OF MULTIPLE CHALAZION - Qurban, Qirat; Zeeshan Kamil; Khalid Mahmood (Journal of Ayub Medical College Abbottabad, 2021)
Background: Being one of the most common eye lid inflammatory lesion, there is an abundance of ways its treatment can be approached; however, the dearth of consensus on its management guidelines still remains a point of interest in peer reviewed literature. Purpose: To evaluate the additional advantage of injecting subtarsal steroid injection simultaneously with incision and curettage of multiple eye lid chalazion. Method: This intervention study was carried out in the Ophthalmology unit of Khalid Eye Clinic, Karachi from February to July 2019 and included fifty patients of both male and female with age ranging between 15-45 years. The patients were distributed into two groups with twenty-five patients in each group. Group A included patients undergoing incision and curettage only for eye lid multiple chalazion, whereas, Group B included patients undergoing incision and curettage with simultaneous subtarsal steroid injection. Post operatively patients were advised to do hot compresses for at least five days and observe the resolution of swelling and recurrence of chalazion for up to six months. Result: The average time for resolution of the swelling in group A patients was 4.4±1.45 days, but eleven out of the twenty-five patients developed chalazion on the same eye lid again within the follow up period. Although group B patients took 6.0±2.7 days for the resolution of swelling but none of them developed recurrent chalazion within the follow up period. Conclusion: Patients undergoing incision and curettage with simultaneous steroid injection proved to have an additional benefit in terms of reduction in recurrence of chalazion.